Un fablab hybride pour l’enseignement des humanités numériques - Stéphanie Marty; Katia Thomas Vasquez (Humanités Numériques)
Digital technology is now central in all sectors of society, and especially at universities, where it is changing didactics and pedagogy. However, few studies have focused on the influence of digital humanities in the implementation of specific programmes to help students succeed. This study aims to fill this gap, by questioning how digital humanities are taught in such programmes. More precisely, we choose to question the assets and limitations, for students and teachers, of an aid system mobilising engineering and rooted in digital humanities teaching. Finally, we consider the potential transferability of this study to other systems, and even to other sectors of the educational world.